Pengaruh Self-Actualization Dan Gaya Hidup Hangout Terhadap Keputusan Pembelian di Kedai Kopi Janji Jiwa Pada Generasi Milenial Bekasi - Sari, Linda Puspita; Hana Mufida Rahmi; Selvy Trisya Hardianti; Retno Purwani Setyaningrum (Jurnal Ekonomi Syariah Pelita Bangsa, 2023)
The purpose of this research was to determine the effect of self-actualization and hangout lifestyle on purchasing decisions at Janji Jiwa Coffee Shop for the Bekasi millennial generation. The study employs a quantitative approach and an associative method. The research sample is obtained using non-probability sampling, involving 100 respondents who are consumers of Kedai Kopi Janji Jiwa and have made at least one purchase. Data collection is conducted through questionnaires, while data analysis utilizes validity tests, reliability tests, and hypothesis testing with the assistance of SmartPLS 4.0. The findings of this research indicate that self-actualization (X1) significantly influences purchase decisions. Additionally, the hangout lifestyle (X2) also has a significant impact on purchase decisions. Both self-actualization and hangout lifestyle significantly influence purchase decisions at Kedai Kopi Janji Jiwa among the millennial generation in Bekasi